Continuous cropping of potato changed the metabolic pathway of root exudates to drive rhizosphere microflora - Xing, Yanhong; Zhang, Pingliang; Zhang, Wenming; Yu, Chenxu; Luo, Zhuzhu (Frontiers in Microbiology, 2024)
For potato production, continuous cropping (CC) could lead to autotoxicity buildup and microflora imbalance in the field soil, which may result in failure of crops and reduction in yield. In this study, non-targeted metabolomics (via liquid chromatography with tandem mass spectrometry (LC-MS/MS) combined with metagenomic profiling (via high-throughput amplicon sequencing) were used to evaluate correlations between metabolomics of potato root exudates and communities of bacteria and fungi around potato plants to illustrate the impacts of CC. Potato plants were grown in soil collected from fields with various CC years (0, 1, 4 and 7 years).